Functional data analysis - Ramsay J O; Silverman B W (New York Springer-Verlag, 2005)
This monograph presents many ideas and techniques for such data. Included are expressions in the functional domain of such classics as linear regression, principal components analysis, linear modelling, and canonical correlation analysis, as well as spec
Keywords: Data analysis; Functional data analysis